Increased Water Content in the Active Layer Revealed by Regional‐Scale InSAR and Independent Component Analysis on the Central Qinghai‐Tibet Plateau - Jie Chen; Tonghua Wu; Lin Liu; Wenyu Gong; Simon Zwieback; Defu Zou; Xiaofan Zhu; Guojie Hu; Erji Du; Xiaodong Wu; Ren Li; Sizhong Yang (Geophysical Research Letters)
Abstract Isolating seasonal deformation from Interferometric Synthetic Aperture Radar (InSAR) time‐series is critical to quantitative understanding the freeze‐thaw processes in permafrost regions. Physics‐ or statistics‐based approaches have been developed to extract seasonal deformation, yet both constraining their evolution in time domain, and thus impeded the quantification of their amplitude variability especially over large scales. By applying Independent Component Analysis (ICA) on Sentinel‐1 InSAR measurements during 2015–2019 on the central Qinghai‐Tibet Plateau, we reveal that the averaged seasonal deformation is increasing with a linear trend of around 0.17 cm/year. The growing seasonal amplitude is attributed to an 8 cm increase of the Equivalent Water Thickness in the active layer. The results demonstrate the capability of ICA‐based decomposition on isolating freeze‐thaw‐related deformation from other components. The large‐scale spatial distribution of varied seasonal deformation can provide new insight into quantifying the water mass balance in vast permafrost regions.